An Overview of the Indian Homoeopathic Medicine Industry (Homoeopathy for All, 2025)
The Indian Homoeopathic Medicine industry, introduced in the 19th century, has grown into a significant part of the country's Healthcare system, recognized as a national system of medicine, with a large number of practitioners and a substantial market size. Homeopathy initially flourished in Bengal, with Calcutta becoming a center for Homoeopathic practice and education. Homoeopathy has become the third most popular method of medical treatment in India, after Allopathy and Ayurveda, with a large nu...
Keywords: Medicine; homeopathy; substantial; Allopathy and Ayurveda